Methane formation driven by reactive oxygen species across all living organisms - Ernst, Leonard; Steinfeld, Benedikt; Barayeu, Uladzimir; Klintzsch, Thomas; Kurth, Markus; Grimm, Dirk; Dick, Tobias P.; Rebelein, Johannes G.; Bischofs-Pfeifer, Ilka; Keppler, Frank (Nature, 2022)
Methane (CH4), the most abundant hydrocarbon in the atmosphere, originates largely from biogenic sources1 linked to an increasing number of organisms occurring in oxic and anoxic environments. Traditionally, biogenic CH4 has been regarded as the final product of anoxic decomposition of organic matter by methanogenic archaea. However, plants2,3, fungi4, algae5 and cyanobacteria6 can produce CH4 in the presence of oxygen. Although methanogens are known to produce CH4 enzymatically during anaerobic energy metabolism7, the requirements and pathways for CH4 production by non-methanogenic cells are poorly understood. Here, we demonstrate that CH4 formation by Bacillus subtilis and Escherichia coli is triggered by free iron and reactive oxygen species (ROS), which are generated by metabolic activity and enhanced by oxidative stress. ROS-induced methyl radicals, which are derived from organic compounds containing sulfur- or nitrogen-bonded methyl groups, are key intermediates that ultimately lead to CH4 production. We further show CH4 production by many other model organisms from the Bacteria, Archaea and Eukarya domains, including in several human cell lines. All these organisms respond to inducers of oxidative stress by enhanced CH4 formation. Our results imply that all living cells probably possess a common mechanism of CH4 formation that is based on interactions among ROS, iron and methyl donors, opening new perspectives for understanding biochemical CH4 formation and cycling.
Das PDF enthält einen Anhang von 18 Seiten
Gesehen am 10.03.2022